Nowcasting the Transportation and Accommodation Sectors Growth using the Google Trends Index - Dhiar Niken Larasati; Nucke Widowati Kusumo Projo (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
This research aims to assess the possibility of the daily and weekly Google Trends Index (GTI) to predict the quarterly GDP growth. The U-MIDAS approach is utilized because it allows using of daily and weekly basis data to forecast quarterly indicators without aggregating them onto a quarterly basis hence it does not eliminate useful information on the daily and weekly data. This research uses quarterly GDP for the transportation sector and the accommodation and restaurant sector which are considered potential industries for the future of Indonesia's economy. The result shows that the daily basis GTI can effectively predict the quarterly GDP growth better than the weekly basis GTI based on the RSE scores.